Analysis of the Influence of Price, Promotion Media, and Quality of Product on Sales of MSMEs in Medan City - Silalahi, Ronaldo Gunawan; Perangin Angin, Cindy Catrine; Loo, Dinda Salsabila; Saragih, Rintan; Saribu, Holfian Daulat Tambun (International Journal Of Economics Social And Technology (IJEST), 2023)
The development of MSMEs in the city of Medan is recorded as a significant development when compared to the surrounding infrastructure support areas such as Deli Serdang, Langkat, Binjai and others. In this study using a quantitative method, according to Sugiyono (2018), the quantitative research method is research based on the philosophy of positivism, used to examine certain populations and samples. This study used 100 samples from Medan Sunggal District, using the cluster sampling method. The results of this study indicate that the product price, promotional media, and product quality variables have a positive and significant effect with the coefficient of determination (Adjusted R Square) of 0.319. This means that the selection is influenced by product price, product promotion, and product quality variables of 31.9%. And in the t test, it is known that the Sig value for influencing product prices on product sales is 0.002 <0.05 and the Tcount value is 3,158 > Ttable 1,985. So it can be stated that product prices have a significant effect on product sales. On the media promotion variable, it is known that the Sig value for influencing media promotion on product sales is 0.035 <0.05 and the Tcount value is 2,140 > Ttable 1,985. So it can be stated that product promotion has a significant effect on product sales. And on product quality it is known that the Sig value for influencing product quality on product sales is 0.000 > 0.05 and the Tcount value is 4,890 > Ttable 1,985. So it can be stated that product quality has a significant effect on product sales.